Antioxidant, membrane stabilizing and thrombolytic potentials of the leaves of erythrina fusca lour - Yahya, Muneera Binta; Arafat, Shahjada; Ahsan, Tanvir; Shahriar, Saimon; A Rashid, Mohammad; Rahman, Mohammad Sharifur (Bangladesh Journal of Botany, 2024)
Erythrina fusca (Family: Fabaceae) is famous for many traditional healing. In the present study, the leaves of E. fusca were collected, dried, powdered and then extracted with methanol. It was further partitioned into n-hexane, dichloromethane and aqueous soluble fractions. All the extracts were subjected to antioxidant, membrane stabilizing and thrombolytic assays. In case of free radical scavenging assay, the aqueous soluble fraction showed highest scavenging activity. In ferric reducing anti-oxidant power assay, the dicholoromethane extract showed highest reduction of ferric ion in a dose dependent manner. In total antioxidant assay, the methanol extract and dichloromethane extract showed stronger capacity as antioxidant. During the determination of total phenolic and flavonoid contents, the methanol extract and dichloromethane soluble fraction showed higher contents of phenolics and flavonoids, respectively. The erythrocyte membrane stabilizing assay revealed the capacities of methanol extract and its aqueous fraction to stabilize the RBC membrane in both hypotonic solution- and heat- induced hemolytic conditions. However, the clot lysis ability of the E. fusca leaf extracts was not so prominent. Bangladesh J. Bot. 53(3): 439-445, 2024 (September)